New Advances in Nanomaterial‐Based Antiviral Strategies. Issue 7 (20th April 2022) - Xu, Xican; Zhang, Jin; Liu, Shuang; Wang, Chaohui; Wang, Hongyu; Fan, Huahao; Tong, Yigang; Liu, Huiyu; Zhou, Dongsheng
Abstract : The ongoing coronavirus disease 2019 (COVID‐19) pandemic and other major viral infectious diseases have become a significant threat to people's life and economic/social development. In recent years, with the development of nanotechnology, nanomaterial‐based antiviral agents have been extensively studied. However, the clinical applications of antiviral nanomaterials are still limited. Herein, the recent advances in nanomaterial‐based antiviral strategies, mainly including antiviral nanodrugs, drug nanocarriers, and nanovaccines, are summarized. The clinical challenges and prospects of nanomaterial‐based antiviral strategies are also discussed. Abstract : Herein, the recent advances in nanomaterial‐based antiviral strategies and their antiviral mechanisms are summarized. The advantages of different antiviral strategies and challenges of antiviral nanomaterials in the clinical translation are also discussed. The aim is to offer inspiration for the development of more effective and broad‐spectrum antiviral strategies and to promote the development of antiviral strategies for clinical use.